2005
DOI: 10.1111/j.1467-789x.2005.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of the metabolic syndrome in obesity

Abstract: The metabolic syndrome is a constellation of interrelated abnormalities that increase the risk for cardiovascular disease and progression to type 2 diabetes. The prevalence of this syndrome is increasing because of the 'obesity epidemic'. The National Cholesterol Education Program Adult Treatment Panel III defined practical criteria for the diagnosis of the metabolic syndrome and established the basic principles for its management. Also, the International Diabetes Federation recently proposed another definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 135 publications
(120 reference statements)
0
70
0
4
Order By: Relevance
“…18,19 Helping the athlete understand the potential role central adiposity plays in overall health may provide motivation to prevent progression of MetSyn into diabetes or heart disease in later life by changing body fat and lean muscle distribution. It may be helpful to share the data from McGill et al 20 and Zieske et al, 21 who demonstrated clear and progressive coronary artery disease occurring linearly with BMI, abdominal adiposity, and elevated CRP in postmortem studies of young people (15-34 years of age) who died of noncardiovascular causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Helping the athlete understand the potential role central adiposity plays in overall health may provide motivation to prevent progression of MetSyn into diabetes or heart disease in later life by changing body fat and lean muscle distribution. It may be helpful to share the data from McGill et al 20 and Zieske et al, 21 who demonstrated clear and progressive coronary artery disease occurring linearly with BMI, abdominal adiposity, and elevated CRP in postmortem studies of young people (15-34 years of age) who died of noncardiovascular causes.…”
Section: Discussionmentioning
confidence: 99%
“…23 The Therapeutic Lifestyle Changes proposed by the National Cholesterol Education Program suggest that saturated fats constitute no more than 7% of total fat calories, with up to 10% of calories from polyunsaturated fats and up to 20% of calories from monounsaturated fats; fats should constitute 25% to 35% of daily calories; and cholesterol consumption should not total more than 200 mg/d. 18,19 Additionally, diets high in simple sugars have been implicated in elevated levels of TGs and depressed levels of HDLs, 24 whereas others 25 have suggested that a diet of high glycemic index foods may contribute to higher levels of fasting insulin. The Therapeutic Lifestyle Changes guidelines recommend 50% to 60% of total calories as carbohydrates and 20 g to 30 g of fiber per day, although the current Dietary Recommended Intake for men in this age group is 38 g of fiber daily.…”
Section: Discussionmentioning
confidence: 99%
“…23 These observations constitute presumptive evidence that increased pancreatic fat is a predictor of impending T2DM in rats. The facts that lifestyle modification, thiazolidinediones and metformin, measures that reduce pancreatic fat content in rodents, 25 are known to reduce the incidence of T2DM in humans, 26,27 suggest a lipotoxic etiology for T2DM in both species. This sets the stage for prospective clinical studies to determine if interventions that reduce pancreatic TG levels will preserve b-cell function and reduce the incidence of T2DM in humans as effectively as they do in rodents.…”
Section: Chronology Of Pancreatic Steatosis Relative To Plasma Insulimentioning
confidence: 99%
“…Lifestyle modification should be recommended in the management of both hypertension and dyslipidaemia. [111][112][113][114] Lipidfriendly (e.g. alpha-blockers) or lipid neutral (calcium antagonists, ACE inhibitors, angiotensin II receptor antagonists 115 ) may be considered in the context of hypertension and dyslipidaemia.…”
Section: Statins and Hypertension Hj Milionis Et Almentioning
confidence: 99%